Immune and Inflammatory Responses of the Intestinal Mucosa following Extended Liver Radiofrequency Ablation. (25th October 2017) - Ypsilantis, Petros; Lambropoulou, Maria; Evagellou, Antonios; Papadopoulos, Nikolaos; Simopoulos, Constantinos
Abstract : Background and Aim . Extended liver radiofrequency ablation (RFA) has been shown to disrupt gut barrier integrity with subsequent bacterial translocation. The aim of the present project was to study the immune and inflammatory responses of the intestinal mucosa after extended RFA of the liver. Methods . Twelve Wistar rats were either subjected to RFA of the left lateral hepatic lobe (approximately 30% of the liver mass) after midline laparotomy (group RFA, n = 6 ) or sham operation (group Sham, n = 6 ). Forty-eight hours later, ileal tissue specimens were excised for immunohistochemical assessment of CD68 + macrophages, CD4 + T-lymphocytes, CD8 + T-lymphocytes, mucosal addressin cell adhesion molecule-1 (MAdCAM-1), tumor necrosis factor- α (TNF α ), interleukin-6 (IL-6), and nuclear factor- κ B (NF κ B) expression. Results . Immune response biomarkers were upregulated in the RFA group. Expression of CD4 + and CD8 + T-lymphocytes was moderate, while that of CD68 + macrophages and MAdCAM-1 was high. Inflammatory response biomarkers were also upregulated in the RFA group. TNF α, IL-6, and NF κ B expression was low, moderate, and high, respectively. Conclusions . Extended liver RFA evokes both immune and inflammatory responses of the gut mucosa.